Validitas Penggunaan Media Komik Digital Terhadap Hasil Belajar IPA Sekolah Dasar - Manda Diva Aulia; Fitria Eka Wulandari (Jurnal Teknologi Pendidikan, 2026)
This study aims to determine the validity level of digital comic learning media (e-comics) on the topic “Plants as a Source of Life on Earth” for science learning in elementary schools. The research used a development research design with a quantitative descriptive approach. The subjects consisted of three validators, namely two subject matter experts and one media expert. Data were collected using a validation sheet that assessed content feasibility, language clarity, presentation, and visual display. The data were analyzed using quantitative descriptive techniques with a percentage formula. The results showed that the digital comic media obtained a validity score of 89.73%, categorized as highly valid. This indicates that the developed media has met the feasibility standards in terms of material accuracy, language appropriateness, systematic presentation, and visual quality. Therefore, the e-comic is considered highly feasible as an alternative media to support science learning in elementary schools.